The Influence Of Supporting Environment On The Independence Of Millennial Farmers Participating In The Yess Program In Sukabumi District: PENGARUH LINGKUNGAN PENDUKUNG TERHADAP KEMANDIRIAN PETANI MILENIAL PESERTA PROGRAM YESS DI KECAMATAN SUKABUMI - risma risma; Ema Hilma Meilani; Endang Tri Astutiningsih (Agrifarm : Jurnal Ilmu Pertanian, 2026)
The Youth Entrepreneurship and Employment Support Services (YESS) Program is a youth development program in the agricultural sector aimed at enhancing the capacity of millennial farmers. However, the low rate of young farmer regeneration and the limited supporting environment remain challenges in agricultural development. This study aims to analyze the relationship between the supporting environment and the independence of millennial farmers participating in the YESS Program in Sukabumi District. The study employed a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. Purposive sampling was used to select 45 respondents. The results showed that the supporting environment had a positive and significant relationship with millennial farmers’ independence, with a path coefficient value of 0.796 and a p-value of 0.000. The findings also indicated that millennial farmers who received better supporting environments tended to have higher levels of independence. The supporting environment variable was measured through indicators of partnership development, rural youth mobilization, and agricultural youth policy. This study provides empirical contributions to the development of millennial farmer studies by examining the role of the supporting environment within the context of the YESS Program using the SEM-PLS approach. Therefore, strengthening partnerships, rural youth mobilization, and agricultural youth policies is necessary to support the sustainability of millennial farmers in the agricultural sector.